2004
DOI: 10.1023/a:1026099523505
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Characteristics and Correction of Long-Term Eddy-Covariance Measurements Over Two Mixed Hardwood Forests in Non-Flat Terrain

Abstract: We present turbulence spectra and cospectra derived from long-term eddy-covariance measurements (nearly 40,000 hourly data over three to four years) and the transfer functions of closed-path infrared gas analyzers over two mixed hardwood forests in the mid-western U.S.A. The measurement heights ranged from 1.3 to 2.1 times the mean tree height, and peak vegetation area index (VAI) was 3.5 to 4.7; the topography at both sites deviates from ideal flat terrain. The analysis follows the approach of Kaimal et al. (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 35 publications
(124 reference statements)
8
53
0
Order By: Relevance
“…7 is 1.2 s. The transfer function found for our system is very similar to empirical transfer functions reported by Goulden et al (1996), Laubach and Teichmann (1996), Leuning and Judd (1996), and Su et al (2004) for water vapour flux measurements with closed path systems using a long inlet tube (materials: polyethylene or Teflon). They all applied a combined CO 2 /H 2 O IRGA instrument for the water vapour detection and observed the strong damping effect only for the H 2 O and not for the CO 2 flux.…”
Section: Atmossupporting
confidence: 86%
See 1 more Smart Citation
“…7 is 1.2 s. The transfer function found for our system is very similar to empirical transfer functions reported by Goulden et al (1996), Laubach and Teichmann (1996), Leuning and Judd (1996), and Su et al (2004) for water vapour flux measurements with closed path systems using a long inlet tube (materials: polyethylene or Teflon). They all applied a combined CO 2 /H 2 O IRGA instrument for the water vapour detection and observed the strong damping effect only for the H 2 O and not for the CO 2 flux.…”
Section: Atmossupporting
confidence: 86%
“…7 for an exemplary day together with the total transfer function of all known damping effects. The observed empirical transfer function can be well described by a first order response function of the following form (Horst, 1997;Su et al, 2004):…”
Section: Atmosmentioning
confidence: 99%
“…Previous studies have shown large high-frequency flux attenuation of traditional closed-path gas analysers (Haslwanter et al, 2009), such as used in this study at the dry heath site, caused by tube walls and tube age (Su et al, 2004;Massman and Ibrom, 2008) and tube length (Novik et al, 2013). Enclosed-path systems, however, reduce flux attenuation compared to traditional closed-path systems due to shorter tube length (Burba et al, 2010;Novick et al, 2013).…”
Section: Energy Balance Closure and System Performancementioning
confidence: 71%
“…These uncertainties and errors have been discussed in detail elsewhere (e.g. Goulden et al, 1996;Moncrieff et al, 1996;Vickers and Mahrt, 1997;Wilson et al, 2002;Su et al, 2004). Here, issues of particular importance in the urban environment are highlighted.…”
Section: Introductionmentioning
confidence: 93%